-5/13.2/11+-5/11.9/13+1

Question

-5/13.2/11+-5/11.9/13+1

in progress 0
Kiệt Gia 10 months 2021-04-27T08:59:41+00:00 2 Answers 8 views 0

Answers ( )

    0
    2021-04-27T09:00:49+00:00

    Đáp án:

    $=\dfrac8{13}$ 

    Giải thích các bước giải:

    $\dfrac{-5}{13}.\dfrac{2}{11}+\dfrac{-5}{11}.\dfrac{9}{13}+1$

    $=\dfrac{-5}{13}.\dfrac2{11}+\dfrac{-5}{13}.\dfrac9{11}+1$

    $=\dfrac{-5}{13}\bigg(\dfrac2{11}+\dfrac9{11}\bigg)+1$

    $=\dfrac{-5}{13}.1+1$

    $=\dfrac{-5}{13}+1=\dfrac8{13}$ 

    0
    2021-04-27T09:01:15+00:00

    `-5/13 . 2/11 + (-5/11) . 9/13 + 1`

    `= -5/13. 2/11 +(-5/13) . 9/11 + 1`

    `= -5/13( 2/11 + 9/11) +1`

    `=-5/13 . 1 + 1`

    `= -5/13 + 13/13`

    `= 8/13`

     

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )